2017
DOI: 10.1017/s0025315417001382
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of the Manila clam (Ruditapes philippinarum): an intensively harvested invasive species in the Tagus Estuary (Portugal)

Abstract: The present study aimed to describe the reproductive cycle and estimate the size at sexual maturity of the Manila clam (Ruditapes philippinarum) in the Tagus Estuary (Portugal). Specimens were collected monthly from September 2013 to December 2015 during fishing surveys using bivalve dredges. The gametogenic cycle was described in detail using gonad histology and monitored throughout the study period by the monthly variation in the frequency of gonad maturation stages, mean gonadal index and mean oocyte diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Since both sexes of the three clam species and the cockle show synchrony in the stages of gonadal development (R. decussatus: Matias et al, 2013;Genez et al, 2015;R. philippinarum: Drummond et al, 2006;Moura et al, 2018;V. corrugata: Joaquim et al, 2011;C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both sexes of the three clam species and the cockle show synchrony in the stages of gonadal development (R. decussatus: Matias et al, 2013;Genez et al, 2015;R. philippinarum: Drummond et al, 2006;Moura et al, 2018;V. corrugata: Joaquim et al, 2011;C.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to a failure in the recruitment that, sustained over time, and together with overfishing (Massapina and Arrobas, 1991;Maia et al, 2006) could be the reason for the decrease of the populations of this clam. Consequently, the introduced Manila clam with faster maturation, greater number of spawning events, longer and greater reproductive activity, faster growth (Laruelle et al, 1994;Delgado and Pérez-Camacho, 2007;Moura et al, 2017Moura et al, , 2018 and greater tolerance to salinity and temperature stress (Domínguez et al, 2020(Domínguez et al, , 2021 contribute to the observed larger abundance of the introduced clam. Furthermore, R. philippinarum, but not R. decussatus, is typically seeded in shellfish beds (e.g., Royo et al, 2002;Melià and Gatto, 2005;Mantovani et al, 2006) artificially increasing its abundance.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of seasonal closures to shellfish harvesting associated to the reproductive cycle is used as a management measure to ensure the replenishment of bivalve stocks. The Manila clam has an extensive spawning period, as was confirmed for the populations in the Ria de Aveiro (Maia et al, 2021) and the Tagus estuary (Moura et al, 2018), starting at the end of spring and extending until autumn. Nevertheless, this type of measure must be comprehensive, in order to protect the various exploitable species that co-occur in the same systems.…”
Section: Regulation Measuresmentioning
confidence: 60%
“…Where to install new waste water treatment plants and where outfalls should be placed (or relocated), should take into consideration the ET and water exchange among areas of the estuary, in order to avoid the retention of large amounts of nutrients in the estuary for long periods of time, to promote their quick flush to the sea, and to improve the microbiological quality of the Tagus estuarine water. Bacterial contamination is a prevalent problem in the Tagus estuary that contaminates shellfish and affects an important harvesting bivalve activity (Moura et al, 2017(Moura et al, , 2018, which occurs prevalently in its main body. Recently, bivalve harvesting was forbidden in one of the most important bivalve fishing areas of the Tagus estuary due to the high levels of contamination of bivalves by Escherichia coli which is causing significant local socio-economic issues.…”
Section: Discussionmentioning
confidence: 99%